2021
DOI: 10.1186/s13068-021-02071-0
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress improves thermotolerance and high-temperature bioethanol production of multi-stress-tolerant Pichia kudriavzevii by stimulating intracellular metabolism and inhibiting oxidative damage

Abstract: Background High-temperature bioethanol production benefits from yeast thermotolerance. Salt stress could induce obvious cross-protection against heat stress of Pichia kudriavzevii, contributing to the improvement of its thermotolerance and bioethanol fermentation. However, the underlying mechanisms of the cross-protection remain poorly understood. Results Salt stress showed obvious cross-protection for thermotolerance and high-temperature ethanol p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The members of the P. kudriavzevii species present as the main mechanism of resistance to thermal stress, the accumulation of trehalose and glycerol. In fact, their ability to tolerate temperatures higher than 37 °C recommends them for a series of industrial processes aimed at obtaining valuable compounds for the food and cosmetic industries, as well as for biomedical applications [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The members of the P. kudriavzevii species present as the main mechanism of resistance to thermal stress, the accumulation of trehalose and glycerol. In fact, their ability to tolerate temperatures higher than 37 °C recommends them for a series of industrial processes aimed at obtaining valuable compounds for the food and cosmetic industries, as well as for biomedical applications [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, N. atacamensis exhibited an increased number of genes associated with oxidative phosphorylation and the TCA cycle, likely suggesting that this yeast may rely on the electron transport chain for ATP production and energy generation via cellular respiration. These differences may correlate with the hyperarid conditions where N. atacamensis is present, where high salt concentrations may increase gene expression in TCA cycle genes due to an increase ATP demand (Lahtvee et al, 2016; Li et al, 2021). Conversely, N. peltata displayed a higher number of genes involved in sulfur metabolism, suggesting an augmented capacity for sulfur assimilation, utilization, and regulation when compared to N. atacamensis .…”
Section: Resultsmentioning
confidence: 99%
“…Branch lengths denote amino acid substitutions per site. correlate with the hyperarid conditions where N. atacamensis is present, where high salt concentrations may increase gene expression in TCA cycle genes due to an increase ATP demand (Lahtvee et al, 2016;Li et al, 2021). Conversely, N. peltata displayed a higher number of genes involved in sulfur metabolism, suggesting an augmented capacity for sulfur assimilation, utilization, and regulation when compared to N. atacamensis.…”
Section: N Atacamensis Whole Genome Sequencingmentioning
confidence: 97%
“…Similarly, inorganic salt ions also have a certain impact on high temperature tolerance: this study found that NaCl, KH 2 PO 4 , MgSO 4 and CaCl 2 could improve the tolerance of yeast under heat stress. Some studies have reported that salt stress can improve the heat tolerance of yeast by stimulating intracellular metabolism and inhibiting oxidative damage [35]. Therefore, the high temperature resistance can be improved by changing the concentration of inorganic salt ions in practical application.…”
Section: Discussionmentioning
confidence: 99%